2006
DOI: 10.1177/00222194060390010601
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spanish Intervention for First-Grade English Language Learners at Risk for Reading Difficulties

Abstract: The effectiveness of an explicit, systematic reading intervention for first-grade students whose home language was Spanish and who were at risk for reading difficulties was examined. Participants were 69 students in 20 classrooms in 7 schools from 3 districts who initially did not pass the screening in Spanish and were randomly assigned within schools to a treatment or comparison group; after 7 months, 64 students remained in the study. The intervention matched the language of instruction of their core reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 48 publications
1
101
1
5
Order By: Relevance
“…Collier (1987Collier ( /1988Collier ( , 1992Collier ( , 1995, Roberts (1994), and Lee and Schallert (1997) among others identified age 9 (grade 4 equivalent, GE 4) as the point at which children can independently access, retrieve, and transfer information stored in these mental frameworks. In the case of literacy development, second-language learners rely on highly similar strategies and underlying processes that transfer at an even younger age (Vaughn, Linan-Thompson, Pollard-Durodola, Mathes, & Hagan, 2006). Mapping new linguistic information onto existing mental frameworks is a far less onerous task than having to construct conceptual information in a language that the learner is still acquiring.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Collier (1987Collier ( /1988Collier ( , 1992Collier ( , 1995, Roberts (1994), and Lee and Schallert (1997) among others identified age 9 (grade 4 equivalent, GE 4) as the point at which children can independently access, retrieve, and transfer information stored in these mental frameworks. In the case of literacy development, second-language learners rely on highly similar strategies and underlying processes that transfer at an even younger age (Vaughn, Linan-Thompson, Pollard-Durodola, Mathes, & Hagan, 2006). Mapping new linguistic information onto existing mental frameworks is a far less onerous task than having to construct conceptual information in a language that the learner is still acquiring.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Esses achados remetem à reflexão de que os sinais descritos na literatura nacionais e internacionais 2,11,15,22 sofrem interferência direta da metodologia de ensino, o que justifica o fato de os fonoaudiólogos juntamente com os professores utilizarem programas de intervenção com base fonológica e na relação letra-som para identificar e intervir precocemente nos sinais da dislexia e, consequentemente, diminuir o número de encaminhamentos desnecessários para a realização de diagnóstico fonoaudiológico. Essa prática corrobora estudos descritos na literatura internacional 16-18,23-27. Assim, os achados deste estudo apresentam o treinamento da habilidade fonológica e correspondência grafema-fonema em crianças de 1ª série com risco para dislexia como um instrumento de auxílio ao diagnóstico de uma condição determinada genética e neurologicamente como a dislexia, uma vez que conforme descrição na literatura internacional 3,5,6,12,13 , o fracasso da criança de risco a este tipo de treinamento é um critério diagnóstico para a dislexia. Esses achados apontam para o fato de que quanto menor for a instrução na base fonológica e da relação letra-som para a aprendizagem da leitura, maior será o risco de os fonoaudiólogos identificarem erroneamente uma criança como sendo disléxica.…”
Section: Discussionunclassified
“…Por isso, estudos internacionais apontam para a necessidade de realização de intervenção precoce em crianças que apresentam desempenho abaixo do esperado em fase pré-escolar e nos dois primeiros anos de alfabetização em relação ao seu grupo-classe nos fatores preditivos para o bom desempenho em leitura, como: conhecimento do alfabeto, nomeação automática rápida, repetição de não-palavras e habilidades de consciência fonológica. Estas crianças são denominadas na literatura internacional como crianças de risco para a dislexia 3,5,6,[11][12][13] . Desta forma, é preciso que tanto professores como fonoaudiólogos estejam atentos ao desenvolvimento da linguagem expressiva e receptiva das crianças no início da alfabetização para que a identificação e a detecção dos sinais da dislexia possam ocorrer precocemente e os problemas acadêmicos decorrentes de alterações cognitivo-linguísticas minimizados por meio da realização de programas de treinamento de habilidades fonológicas associado à correspondência grafema-fonema.…”
Section: Introductionunclassified
“…By the year 2050, the total U.S. population will have doubled from its present levels, with approximately one-third of the increase attributed to immigration. Vaughn, et al (2006) found that English language learners are the fastest growing group in the U.S. public schools and Spanish speaking students represent the highest number of ESL students. The U.S. Department of Education (2002) indicates that there are four million students with limited English proficiency and nearly 80 percent identifying as Latino and another 20 percent representing other languages.…”
Section: English As a Second Language Studentsmentioning
confidence: 99%
“…This struggle is difficult as ESL learners are fearful of giving up cultural identity but also fearful of rejection by their peers. Vaughn et al (2006) found that ESL learners desired to learn the English language while still preserving their own cultural identity. In addition, students whose parents enjoy higher socioeconomic status are more likely to identify with their parents' nationality than are their poorer co-nationals/co-ethnics (Rumbaut, 1996).…”
Section: English As a Second Language Studentsmentioning
confidence: 99%